Functional diversity literacy. Issue 2 (11th June 2018) - Pionke, JJ
Abstract : Purpose: The purpose of this paper is to discuss the problematic nature of librarian attitudes toward people with disabilities and how a language change to the use of the term "functionally diverse" can highlight a greater sense of inclusion and equality, as well as develop a new type of literacy that focuses on understanding and awareness of disabilities, accessibility and difference. Design/methodology/approach: This paper examines current trends of language use about people with disabilities and then posits a counterpoint by discussing functional diversity as a viable alternative in not just language but also literacy. Findings: Examples of current problematic language by librarians are drawn from social media and the literature. The examples are deconstructed in regard to why they are problematically exclusive, and then the alternative language of functional diversity is examined as a way to be more inclusive. Developing a new literacy in terms of interaction with functionally diverse people is also discussed. Originality/value: Library literature on disability largely focuses on a case study approach and on the view of how to assist people with single disabilities. This is one of the very few papers that focuses on discussing the underlying attitudes and assumptions of librarians that make outreach to people with disabilities who use libraries, difficult. This is also one of the few papers that discusses the need for a new type of literacy within librarianship.